MANAGEMENT OF BREAST CANCER WITH BRCA GENE MUTATION - Ari Sumardika, I Wayan; Sudarsa, I Wayan (E-Jurnal Medika Udayana; vol 2 no 9 (2013):e-jurnal medika udayana, 2013)
Normal 0 false false false EN-US X-NONE X-NONE The management of individual who has a genetic predisposition for breast cancer requires careful planning. It is estimated that 5-10% of breast cancer in Western countries is a hereditary breast cancer and 80-90% of them is the result of BRCA1 and BRCA2 genes mutations. The individual with BRCA1 and BRCA2 gene mutations have a high risk for experiencing breast cancer and other types of cancer, especially ovarian cancer. Although there are some differences, management of patients with hereditary breast cancer in principle is equal to management of non-hereditary breast cancer. Contra lateral mastectomy surgery and/or oophorectomy may be considered as initial therapy. The uses of breast conserving surgery in patients with BRCA-positive status are still controversial because of the risk of recurrence on ipsilateral breast, so did the use of ionization radiation modalities. Post surgery follow up is an important aspect in the management of patients with mutations of these genes in which follow up aims to find local recurrence, secondary breast cancer, contra lateral breast cancer as early as possible /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: breast cancer, management, BRCA 1 and BRCA2 gene